Arterial liver supply in aspect of right lobe living donor liver transplantation: anatomical variants and reconstruction - S. E. Voskanyan; I. Yu. Kolyshev; A. N. Bashkov; A. I. Artemyev; V. S. Rudakov; M. V. Shabalin; M. V. Popov; A. I. Sushkov; G. V. Vohmyanin (Трансплантология (Москва), 2024)
Background. A safe removal of the liver right lobe and restoration of arterial blood supply to the liver graft is possible only with a full understanding of the anatomy of the hepatic artery in a donor.Objective. To describe new and extend contemporary data on anatomical variations of the arterial blood flow in a donor of the right liver lobe.Material and methods. From 2009 to 2021, 306 living donor liver transplantations were performed in the State Research Center – Burnasyan Federal Medical Biophysical Center of Federal Medical Biological Agency. The vascular anatomy of 518 potential donors was analyzed. Hepatic artery anatomical variants of a right lobe graft were assessed.Results. Eleven types of right lobe arterial supply and 7 subtypes of the arterial anatomy of liver segment 4 were identified. The case rates of types and subtypes where reconstruction could be performed were following: type A, subtypes 1, 2, 3, 4, 5 (57.5%, 26.1%, 5.5%, 1.9%, 0.3%, respectively); type B, subtypes 1, 4, 5 (0.3% each); type С, subtypes 1, 2 (2.9%, 1.3%, respectively); type D, subtypes 1, 3 (0.3% each); type Е subtype 1 (0.6%), types F-J subtype 1 (0.3% each). Liver right lobe harvesting and arterial reconstructions were fully performed in all types and subtypes excluding anatomical type K, subtype 7. Arterial postoperative complications (11 cases) were detected in 3.5% observed cases of 306 transplants and in 5.9% of all patients with complications (184). Mortality rate due to arterial complications was 1.9% (6 cases).Conclusion. The existing classification of right liver graft hepatic artery anatomy was updated and detailed regarding the applicability in right lobe liver transplant. The arterial anatomy of right lobe liver graft shows great variability and complexity for systematization and thus may need further studies.